Presentation: Displaced by violence - Flores Lizana, Carlos (2001)
As the title of the journal says, our articles are related to the topic of State policies in communities that suffered political-military violence during the so-called internal war years, that is, 1930-1996. The Truth and Reconciliation Commission, which has begun its work these days, has placed in the national opinion in the first place precisely the issue of the effects of violence on peasant communities, especially in the Andean region, and that it made the State as guarantor of the rights of individuals and communities.